Argumen Logis tentang Eksistensi Tuhan dalam Wacana Filsafat Ketuhanan - Gede Agus Siswadi (Sanjiwani: Jurnal Filsafat, 2021)
Talking about God will have no end, because after all, humans have a tendency to admit that there is a transcendent. This tendency cannot be separated from the various weaknesses inherent in humans. An interesting question from the philosophy of divinity is whether God really exists or is it merely an illusion or human projection. This article seeks to explore and record evidence related to the existence of God. The results of this paper are (1) ontological arguments that show God exists based on the definition of God, (2) cosmological arguments which explain that the creation of this universe and the very regular motion of nature, (3) design arguments, which are based on God is a smart designer (4) moral argument is explained that God is the result of thought, namely that there is no sense in having a moral command, otherwise God governs the moral command, (5) teleological argument based on the purpose of goodness.